2012
DOI: 10.4103/0378-6323.98076
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among schoolchildren with acne: Results of a cross-sectional study

Abstract: The CADI and the CDLQI questionnaires represent simple and reliable instruments for the assesment of HRQoL among schoolchildren with acne. In this study, we identified 17% of boys and 18% of girls perceived their acne as a major problem. It is important to detect and treat such adolescents on time to reduce the psychosocial burden associated with acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 16 publications
10
43
4
2
Order By: Relevance
“…This result is in accordance with the finding of a Greek study (59.2%) 16 , but it is significantly lower than in several other studies with the range from 70.0% to over 90% 9,[17][18][19][20] . We have to mention that a significantly higher acne prevalence was in Užice (73.6%) than in Belgrade (39.6%), without any reasonable explanation for this finding.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in accordance with the finding of a Greek study (59.2%) 16 , but it is significantly lower than in several other studies with the range from 70.0% to over 90% 9,[17][18][19][20] . We have to mention that a significantly higher acne prevalence was in Užice (73.6%) than in Belgrade (39.6%), without any reasonable explanation for this finding.…”
Section: Discussionsupporting
confidence: 94%
“…The results of our study revealed that majority(53.2%) of the participants belonged to the age group 16-20 years which is similar to a study by Jancovic et al which showed that acne prevalence is more at the age of 16 and 17 years 22 .According to Balakrishnan et al acne is a chronic disease affecting 85% of the teenagers. 1 In our study the number of males was more than females which is similar to a Chinese study which reported that acne in adolescents was predominant in males and adult acne was common in females.…”
Section: Discussionsupporting
confidence: 79%
“…1,5,7,8 CADI is a questionnaire which is specific for acne and contains 5 questions-related to the last month-about feelings, interference with social life and interaction with the opposite gender, avoidance of public places, appearance of the skin and perceived severity of disease state.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Measurement of quality of life changes gives insight into the impact of acne from a patient's perspective and can also measure treatment success. 6,7 This study was carried out to determine the impact of acne and its clinical severity on quality of life among patients of different grades of acne patients in various age groups using two questionnaire Cardiff acne disability index (CADI) and Dermatology life quality index (DLQI).…”
Section: Introductionmentioning
confidence: 99%